Investigating Kaldor’s Theory in ASEAN-5 Countries - Phany Ineke Putri; Malik Cahyadin; Basem Ertimi (Universitas Negeri Semarang, 2024)
Manufacturing is a strategic key sector in driving a country's productivity, which will increase per capita income. However, manufacturing has lost its relative role in both developed and developing countries. Five countries in the Southeast Asia region, namely Malaysia, Thailand, Indonesia, the Philippines, and Vietnam are five countries in the middle-income category that have the largest Gross Domestic Product (GDP) in the Southeast Asia region. Based on World Bank data 2023 states that GNI per capita in 2023, namely Indonesia is ranked 112th, Thailand is ranked 80th, Malaysia is ranked 60th, the Philippines is ranked 113th, and Vietnam is ranked 131st. This study aims to analyze the influence of the variables Manufacturing, Foreign Direct Investment, Liner Shipping Connectivity Index, Mobile-cellular Telephone Subscriptions, and Education Index on Gross National Income per capita in five Southeast Asia countries from 2013 to 2022. Using panel data analysis, it is explained that the panel data regression estimation model Fixed Effect Model (FEM) shows an adjusted R2 value of 0.9833. The variables in this study have a significant effect on GNI per capita, namely the variables Manufacturing, Foreign Direct Investment, Liner Shipping Connectivity Index, Mobile-cellular Telephone Subscriptions, Education Index.